2013
DOI: 10.1371/journal.pone.0072350
|View full text |Cite
|
Sign up to set email alerts
|

Free-Living Turtles Are a Reservoir for Salmonella but Not for Campylobacter

Abstract: Different studies have reported the prevalence of Salmonella in turtles and its role in reptile-associated salmonellosis in humans, but there is a lack of scientific literature related with the epidemiology of Campylobacter in turtles. The aim of this study was to evaluate the prevalence of Campylobacter and Salmonella in free-living native (Emys orbicularis, n=83) and exotic ( Trachemys scripta elegans, n=117) turtles from 11 natural ponds in Eastern Spain. In addition, different types of samples (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 49 publications
3
47
0
10
Order By: Relevance
“…enterica. This serovar of Salmonella was also found to be predominant by other investigators (Pedersen et al 2009;Percipalle et al 2011;Nowakiewicz et al 2012;Marin et al 2013). Pasmans et al (2005) examined 44 serotypes of Salmonella enterica from pet reptiles and found that all were able to invade human intestinal epithelial cells and could cause a disease, depending on the age of individual and their immune status.…”
Section: Iguana Iguana Pogona Vitticeps Morelia Viridis) Than Othermentioning
confidence: 68%
See 1 more Smart Citation
“…enterica. This serovar of Salmonella was also found to be predominant by other investigators (Pedersen et al 2009;Percipalle et al 2011;Nowakiewicz et al 2012;Marin et al 2013). Pasmans et al (2005) examined 44 serotypes of Salmonella enterica from pet reptiles and found that all were able to invade human intestinal epithelial cells and could cause a disease, depending on the age of individual and their immune status.…”
Section: Iguana Iguana Pogona Vitticeps Morelia Viridis) Than Othermentioning
confidence: 68%
“…This may reflect different ecological behaviours and feeding habits. However, based on the results obtained by others investigators (Kuroki et al 2013;Krautwald-Junghanns et al 2013;Marin et al 2013;Pasmans et al 2005;Sting et al 2013) it is difficult to state exactly what kinds of S. enterica subspecies are rarely isolated from reptiles, from which other uncommon Salmonella subspecies are often isolated. This huge serovars sectrum of Salmonella strains isolated from reptiles may pose a hazard to human health because it is difficult to predict which kind of Salmonella enterica may be carried in a particular reptile pet.…”
Section: Iguana Iguana Pogona Vitticeps Morelia Viridis) Than Othermentioning
confidence: 99%
“…Other wild animals tested for the presence of Campylobacter species include small rodents, deer, moose, reindeer, boars, mangabeys, porcupines, duikers, and turtles-all were found to have low levels or to be free of Campylobacter species (355,(358)(359)(360)(361)(362). Furthermore, a number of studies have suggested that the importance of wild animals as a reservoir of infection is limited, as strains isolated from wild animals are usually not clonally related to isolates from humans and chickens (317,363,364).…”
Section: Wild Animalsmentioning
confidence: 99%
“…In contrast, isolation of S. enterica subsp. diarizonae from lambs of one flock has indicated an outbreak of disease caused by that organism, which is a pathogen of wild boar and reptiles (Chiari et al, 2013;Marin et al, 2013;Wikström et al, 2014;Touloudi et al, 2015). Environmental infection into the farm barns might have led to subsequent infection of the newborns.…”
Section: Discussionmentioning
confidence: 99%